Social impacts of natural disasters in Africa - Mackay, Robert Martin (Curtin University, 2024)
Natural disasters continue to adversely impact the lives of individuals, especially those in developing countries. Using large quantitative datasets, this multi-country individual-level analysis of the social consequences of disaster exposure focuses on the African continent. It also features analysis of primary collected data in Kenya. The results show that while exposure to disaster results in greater collective coping, it also significantly reduces generalised trust, and generates more routine experiences with crime.